Understanding the structural behavior of historical buildings through its constructive phase evolution using H-BIM workflow - Calì, Alfredo; Dias de Moraes, Poliana; Do Valle, Ângela (Journal of Civil Engineering and Management, 2020)
Knowledge is fundamental to understand the key characteristics of a heritage building. Furthermore, constructive analysis of a historical construction is central to research into its structural behavior. This work aims to increase the knowledge level of a historical construction by the understanding of the constructive evolution through Historical-Building Information Modeling (H-BIM) workflow. The research proposes a multidisciplinary approach applicable to the field of historical constructions, which is resumed in the followings steps: historical-critical analysis, material and soil characterization, data organization through H-BIM, qualitative static and dynamic structural analysis, validation of the results. The building of Quartel da Tropa – located in Florianópolis, Brazil – is used as a practical case study to show how the proposed research can be adapted to historical buildings. Such an impressive eighteen-century masonry construction is the largest troop barracks among Brazilian fortifications. The proposed approach allows the creation of a structural model from the architectural model with fewer uncertainties and less simplification, improving the knowledge path of historical constructions and its structural assessment. The historical-critical analysis and the H-BIM allow managing and presenting of the information useful to the understanding of the constructive phase evolution of a historical building.